KØBENHAVN - Christensen, Gunvor (Tidsskriftet Antropologi, 2003)
In this article I present findings of a phenomenological study of the relationship between urban space, sexuality and gender. I have investigated conditions of urban spaces in which social gatherings established among equal and perceptived adults expressing their sexual lusts and pleasures are allowed and encouraged. I have characterised these urban spaces as queer spaces. In the first part, I present circumstances that have imperative significance to the existence of queer spaces, and I argue that queer spaces exist in the metropolis and because of the metropolis. Hereafter, I expound the yearnings that are related to queer spaces and point out that for some individuals queer space equals an emancipated and at the same time an oppositional space to other urban spaces. For other individuals queer space is taken as a parallel space to other urban spaces. These different connotations to queer spaces are related to a dichotomy of either keeping a queer sexuality a secret or being open about it. Finally, I suggest that queer space serves as home territory recognised by being something in between the wide, open urban space, and the intimate, private space, and this unique trait of queer space contributes to a redefinition of the positions of men and women in their sexual performances in public.